Prevention of internalizing disorders and suicide via adolescent sleep interventions. (August 2020) - Blake, Matthew J; Allen, Nicholas B
Abstract : Sleep problems are major risk factors for the development of internalizing disorders and suicidal thoughts and behaviors in adolescents. Emerging evidence suggests that cognitive-behavioral interventions should be considered as a first-line treatment for adolescent sleep problems, and can also address associated mental health concerns. Specifically, several randomized controlled trials have demonstrated that cognitive-behavioral sleep interventions improve mental health in adolescents (particularly anxiety and depression) by improving sleep problems. Although sleep difficulties have been shown to be strong prospective predictors of suicide risk, further studies are needed that examine the efficacy of sleep improvement interventions in reducing suicidal thoughts and behaviors.